External Supervision Of The Judicial Commission Of Judges In Indonesia - Herry Febriadi (Jurnal Penegakan Hukum Indonesia, 2023)
Writing this made for knowing effectiveness Commission Judicial in supervision against judges in Indonesia and the causes Thing that . Case - case prosecution of judges who violate code judge ethics and violate law already Becomes phenomenon moment this . Method research used _ in this article is " research " law normative / juridical normative , data which obtained analyzed by descriptive qualitative . Analysis descriptive qualitative that is method data analysis grouping and selecting data primary in the form of law , then connected with theory - theory , principles , and rules law which obtained from studies related literature _ with object study that is Commission judicial , so that obtained answer on formulated problem . _ From result study meant found answer that role Commission Judicial in skeleton supervision against the judges yet effective . This thing caused by because among them no have authority for drop punishment administration alone to judge and no have authority investigation to para judge which proven in in inspection violate rule criminal .